New Modulators for IGF-I Activity within IGF-I Processing Products - Brisson, Becky K.; Barton, Elisabeth R. (Frontiers in Endocrinology, 2013)
Insulin-like growth factor I (IGF-I) is a key regulator of muscle development and growth. The pre-pro-peptide produced by the Igf1 gene undergoes several post-translational processing steps to result in a secreted mature protein, which is thought to be the obligate ligand for the IGF-I receptor. However, the significance of the additional forms and peptides produced from Igf1 is not clear. For instance, the C-terminal extensions called the E-peptides that are part of pro-IGF-I, have been implicated in playing roles in cell growth, including cell proliferation and migration and muscle hypertrophy in an IGF-I receptor independent manner. However, the activity of these peptides has been controversial. IGF-IR independent actions suggest the existence of an E-peptide receptor, yet such a protein has not been discovered. We propose a new concept: there is no E-peptide receptor, rather the E-peptides coordinate with IGF-I to modulate activity of the IGF-I receptor. Growing evidence reveals that the presence of an E-peptide alters IGF-I activity, whether as part of pro-IGF-I, or as a separate peptide present. In this review, we will examine the past literature on IGF-I processing and E-peptide actions in skeletal muscle, address the previous attempts to separate IGF-I and E-peptide effects, propose a new model for IGF-I/E-peptide synergy, and suggest future experiments to test if the E-peptides truly modulate IGF-I activity.